Depinning assisted by domain wall deformation in cylindrical NiFe nanowires - Chandra Sekhar, M. (2014)
We report on transverse domain wall (DW) depinning mechanisms at the geometrical modulations in NiFe cylindrical nanowires. The DW depinning field and current density always follow opposite trends with diameter modulation. For current driven DW, the depinning current density decreases with increasing notch depth. This interesting behavior arises due to a combination of DW deformation and rotation at the pinning site. With increasing anti-notch height, two distinct depinning mechanisms are observed for both field and current driven DW. Above a critical height, the DW transformation from transverse to vortex configuration leads to a change in the potential barrier. For field-driven, the barrier is lowered, whereas for current-driven, the barrier increases. The increase in the potential barrier for the current driven DW is due to the appearance of an intrinsic pinning within the anti-notch.